2014
DOI: 10.1371/journal.pone.0094974
|View full text |Cite
|
Sign up to set email alerts
|

Human Immune Responses to H. pylori HLA Class II Epitopes Identified by Immunoinformatic Methods

Abstract: H. pylori persists in the human stomach over decades and promotes several adverse clinical sequelae including gastritis, peptic ulcers and gastric cancer that are linked to the induction and subsequent evasion of chronic gastric inflammation. Emerging evidence indicates that H. pylori infection may also protect against asthma and some other immune-mediated conditions through regulatory T cell effects outside the stomach. To characterize the complexity of the CD4+ T cell response generated during H. pylori infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…IL‐6 is the most abundant cytokine during prolonged and uncontrolled activation of inflammation (Mauer et al ., ). Overexpression of IL‐6 was reported in H. pylori infection by others studies (Zhao et al ., ; Zhang et al ., ). Concerning treatment effect, Ando et al .…”
Section: Discussionmentioning
confidence: 97%
“…IL‐6 is the most abundant cytokine during prolonged and uncontrolled activation of inflammation (Mauer et al ., ). Overexpression of IL‐6 was reported in H. pylori infection by others studies (Zhao et al ., ; Zhang et al ., ). Concerning treatment effect, Ando et al .…”
Section: Discussionmentioning
confidence: 97%
“…An EpiBar is a single 9-mer frame containing binding motifs for at least four different HLA alleles (Figure 3). In retrospective evaluations of published promiscuous epitopes, we have found this pattern to be a signature feature of highly immunogenic, promiscuous class II epitopes [53,54].…”
Section: Epitope Mapping Using Computational Toolsmentioning
confidence: 93%
“…Significant advancements in immunome-derived, epitopedriven vaccines designed using the iVAX toolkit have been made in recent years; in particular, basic research studies have demonstrated the ability of the tools to select epitopes for Burkholderia species, 29 H. pylori 30 and HCV, [31][32][33] and validated the importance of the presence of T cell epitopes in subunit vaccines. Recently, the collaborating groups at EpiVax and iCubed discovered epitopes that activate T regulatory cells (Tregs) in viral pathogens using the JanusMatrix tool.…”
Section: Computational Vaccinologymentioning
confidence: 99%